Penguatan Kompetensi Guru Matematika dalam Pengembangan Media Pembelajaran Animasi Berbasis Komputer - Emy Siswanah (LP2M of Institute for Research and Community Services - UIN Walisongo, 2017)
The role of learning media, especially animation media, is very important in learning mathematics especially to explain abstract problem become concrete, motivate student, stimulate student learning activity, help effectiveness of learning process. Community service activities are aimed at making teachers able to create self-directed learning media. By making their own, the teacher can increase his insight and improve his creativity in creating animation media. In this training, teachers are trained to make animation media using powerpoint and flash. Subjects assisted in this devotional activity are math teachers in Semarang City. The math teachers showed great enthusiasm in training and felt the tangible benefits of community service. Teachers can create their own animated learning media, using either powerpoint or flash.